The Study Of Efficacy Of Oral Khadiradi Vati In Tundikeri W.R.T Acute Tonsillitis - Jorvekar, Amruta Sagar; Pathan, Saniya Yusufkhan; saraf, Rhuta Naimish; Saraf, Naimish kishor; Pathare, Smita Sanjay (Journal of Neonatal Surgery, 2025)
Intoduction: The inflammatory condition of tonsil is known as Tonsillitis. Multifocal aetiology that combines together to lower the immunity of the body and this in turn causes Acute Tonsillitis. Acute Tonsillitis can be compared with Tundikeri as there is marked resemblance in their symptoms. Different medical faculties with various therapies have tried in this disease with limited success or time bound relief. ENT specialist recommends tonsillectomy for recurrent attacks of tonsillitis but it has less detrimental effect on the local IgA response in the nasopharyngeal fluid. The former available conservative treatments are antimicrobials, analgesics, and anti-inflammatory drugs used to treat this disease, which accounts for large proportion of health care cost. Besides this, above drug also have limitations and side effects. The increasing refractory nature of infection caused by recently appearing drug resistant bacteria is a particular major clinical problem and to overcome above limitations and side effects it becomes necessary to elucidate another safe, economical and cheap therapy to treat tonsillitis and give better results, so a lot of can be done to support and attain tonsillar health naturally through the traditional way. Khadiradi Vati (Gutika) is an ayurvedic herbal remedy used for mouth ulcer, pharyngitis (sore throat) and other diseases of teeth, gums, tongue and throat. Khadiradi vati acts as an oral anti-septic anti-inflammatory, astringent & expectorant. Therefore, it is beneficial especially in sore throat & tonsillitis or infections of tonsils. Material And Methods: Total 60 patients were randomly selected having age between 10-60 yrs and was divided into 2 equal groups. Trial group were given oral khadiradi vati thrice a day While control group were given yashtimadhu vati thrice day. Appropriate statistical test is applied to evaluate the effect of khadiradi vati in Tundikeri w.r.t. acute tonsillitis. Results And Discussion: Khadiradi Vati has Deepan, Pachan, Swedan, Vilayan properties, which in effect causes Kapha Shaman. Yashtimadhu Vati in control group which is a proven antimicrobial anti-inflammatory drug. Culture and sensitivity of throat swab of patients was done and it observed that Khadiradi vati has antimicrobial property. Oral Khadiradi vati is having Katu Rasa, Ushna Veerya, Tikshna Ushna Guna. It helps in the radical removal of toxic substances from the body. They cause the separation of the matters obstructing the Strotas and dialate them. Above properties of Khadiradi vati results in Amashaya Gata Kapha Dosha Shamana and also rejuvenate Rakta Dhatu, so Samprapti Bhang of Tundikeri Vyadhi Occurs resulting in Shamana of vyadhi lakshanas hence effective in Tundikeri. Conclusion: Oral Khadiradi Vati is effective than control group in Tundikeri. It is safe, cost effective and easy procedure to perform. It decreases severity of throat infection. Hence the role of drug in this disease is proved.